1998
DOI: 10.1021/bi981210f
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of AmpC β-Lactamase from Escherichia coli Bound to a Transition-State Analogue:  Possible Implications for the Oxyanion Hypothesis and for Inhibitor Design

Abstract: The structures of AmpC beta-lactamase from Escherichia coli, alone and in complex with a transition-state analogue, have been determined by X-ray crystallography. The native enzyme was determined to 2.0 A resolution, and the structure with the transition-state analogue m-aminophenylboronic acid was determined to 2.3 A resolution. The structure of AmpC from E. coli resembles those previously determined for the class C enzymes from Enterobacter cloacae and Citrobacter freundii. The transition-state analogue, m-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 47 publications
(81 reference statements)
4
155
0
Order By: Relevance
“…Boronic acids have been recognized as specific inhibitors of AmpC ␤-lactamases since 1982 (4,8,34,37,41). Using three commercially available boronic acids, APB, NPB, and TPB, in the present study, we evaluated three different methods for the identification of bacteria producing class C ␤-lactamases which would be simple enough for routine use in a clinical microbiology laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boronic acids have been recognized as specific inhibitors of AmpC ␤-lactamases since 1982 (4,8,34,37,41). Using three commercially available boronic acids, APB, NPB, and TPB, in the present study, we evaluated three different methods for the identification of bacteria producing class C ␤-lactamases which would be simple enough for routine use in a clinical microbiology laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Serial studies revealed the structure-based mechanism of inhibition of AmpC ␤-lactamases by boronic acids (34,37,41), and novel compounds that inhibit AmpC ␤-lactamases with nano-molar K i values were prepared by stereoselective organic synthesis (23). However, there are only a few reports of studies that applied boronic acids to the identification of class C ␤-lactamase-producing bacteria (19,34).…”
mentioning
confidence: 99%
“…AmpC from Escherichia coli was expressed and purified to homogeneity, as described. 6 Compound 1 was obtained from Aldrich Chemical, Milwaukee, WI. Compounds 2-4 were obtained from Lancaster Synthesis, Windham, NH.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the structure of AmpC has been determined in complex with inhibitors such as -lactams, 4,[20][21][22] transition state analogues, 23,24 and arylboronic acids, 6,25,26 the leads for which were known before the first structures were determined. 27 There are now 18 inhibitor complex structures with class C -lactamases that have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an Escherichia coli K12 AmpC -lactamase [26] was used for all experimental activities. The concentration of AmpC was determined spectrophotometrically in concentrated stock solutions made from lyophilized powder and subsequently diluted; this enzyme had been previously expressed and purified, as described by Powers et al [27].…”
Section: The Performed Experimental Activitiesmentioning
confidence: 99%